Screening for Resistance Against the Sugarbeet Root Maggot, Tetanops myopaeformis (Diptera: Ulidiidae), Using a Greenhouse Bioassay. Issue 3 (1st June 2018) - Daley, Tucker B; Wenninger, Erik J
Abstract: The sugarbeet root maggot, Tetanops myopaeformis (von Röder) (Diptera: Ulidiidae), is a major pest of sugar beet Beta vulgaris L. (Carophyllales: Amaranthaceae)in the United States and Canada. Larval feeding on roots can reduce both stand and yield. Current management practices are heavily reliant on chemical control. However, the carbamate and organophosphate insecticides that are commonly used against T. myopaeformis are being phased out of use. Host plant resistance against this pest shows promise, but difficulties with maintaining T. myopaeformis in culture have largely limited such studies to the field. A primary objective of this study was to develop protocols for rearing a laboratory colony of T. myopaeformis that would expedite assays aimed at screening for host plant resistance. Third (final) instar larvae were collected from the field and reared to the adult stage. These laboratory-reared adults laid eggs and ultimately produced a second generation of third-instar larvae in the lab. Adult flies reared from field-collected larvae were used to examine the modality of resistance of a known resistant variety by performing no-choice and paired-choice experiments alongside a susceptible variety in the greenhouse. Paired-choice tests showed no difference in oviposition rates between the two varieties, whereas no-choice tests showed significantly greater feeding damage and abundance of larvae on the susceptible variety. For the resistant variety examined here, we observed evidence of antibiosis, not antixenosis, as the putative modality of resistance. Our laboratory and greenhouse protocols can be used to expedite the process of developing varieties with resistance to this key pest of sugar beet.